Participation of local communities in conservation of mangrove forest at Kuching Wetlands, Sarawak - Mohammad Tinggal, Mohd Ikhsannuddin (2016)
The mangrove forest areas at Kuching Wetland, which is a Ramsar site, is being exploited at an increasing rate even though conservation programs are extended to the communities. This study is carried out to determine the factors that influence the participation of the local communities in conservation of the mangrove forest resources. 365 respondents were interviewed from seven villages nearby Kuching Wetland National Park. The data were collected using face-to-face interviews of the households‘ representatives at the selected villages using convenient survey technique. Using multiple regression analysis, factors like socio-demographics, economic income, resources, conflicts, knowledge and awareness were tested to determine the influence on the participation. Three factors were identified that influence the participation of local communities, which include knowledge, memberships organization and certain villages. The results reveal that knowledge, location of the wetland and memberships in voluntary organizations have significant relationship with participation in conservation. The study shows that the majority of the members of the communities who are living near the mangrove forest in Kuching Wetlands National Park show positive attitudes towards conservation of mangrove forest resources. Education and awareness campaign for the new generations should be extended to the local communities to enhance their participation in the conservation of the mangrove forest at Kuching Wetland.